2017
DOI: 10.1039/c7ra06615e
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-chemotherapy for cervical cancer treatment with camptothecin loaded Fe3O4 functionalized β-cyclodextrin nanovehicle

Abstract: We portray a novel way to synthesis of iron oxide magnetic nanoparticle incorporated β-cyclodextrin (β-CD) nanocarrier stabilized by ethylenediamine tetra acetic acid (EDTA) obtaining remarkable biocompatibility and biodegradability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…The IC 50 values of the nano-conjugates were much lower than that of the free CPT solution, which can be attributed to the increased solubility of CPT by nano-conjugation. The results were consistent with previous research that demonstrated CPT-conjugated NPs had a higher cell inhibition effect than free CPT against cervical cancer 30 and colon cancer. 31…”
Section: In Vitro Cytotoxicitysupporting
confidence: 93%
“…The IC 50 values of the nano-conjugates were much lower than that of the free CPT solution, which can be attributed to the increased solubility of CPT by nano-conjugation. The results were consistent with previous research that demonstrated CPT-conjugated NPs had a higher cell inhibition effect than free CPT against cervical cancer 30 and colon cancer. 31…”
Section: In Vitro Cytotoxicitysupporting
confidence: 93%
“…Increase in the duration of the drug exposure decreased the viability of the cells, which implies the release of the drug into the medium as the time increases and had impact on the cells. Rajan et al [ 47 ] have also found camptothecin loaded magnetite nanoparticle to induce apoptosis against HeLa cells and they found magnetite to be a better drug delivering agent.…”
Section: Resultsmentioning
confidence: 99%
“…Nanotechnology is exploited in the field of biomedical application for imaging, targeted drug delivery, biosensors, treatment, etc. [5,6]. Apart from these, it has also found applications in environmental for cleaning up environmental pollutants [7], dye removal [8][9][10], waste water treatment [11], heavy metal removal [12], etc.…”
Section: Introductionmentioning
confidence: 99%